High Emergence of Multidrug-Resistant Sequence Type 131 Subclade C2 among Extended-Spectrum β-Lactamase (ESBL)-Producing Escherichia coli Isolated from the University Hospital Bratislava, Slovakia - Ján Koreň; Michal Andrezál; Elham Ozaee; Hana Drahovská; Martin Wawruch; Adriána Liptáková; Tibor Maliar (Antibiotics, 2023)
The expansion of sequence type 131 (ST131) extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) represents major worldwide challenges. E. coli strains originating from healthcare facilities (labeled No. 1 and No. 2) of the University Hospital Bratislava (UHB) were analyzed for ST131 emergence, including its (sub)lineages and clonal relatedness. Antimicrobial resistance was determined in most strains. Of a total of 354 E. coli strains, 263 (74.3%) belonged to ST131; of these, 177 (67.3%) were from No. 1. Generally, among 260 ST131 E. coli, clades A/B were confirmed in 20 (7.7%), while clade C was noted in 240 (92.3%) strains; within them, subclades were detected as follows: C0 (17; 7.1%), C1 (3; 1.2%), and C2 (220; 91.7%). Among fifteen randomly selected E. coli strains that were investigated for ST and clonal relatedness, seven STs were identified: eight (53.3%) ST131, two (13.3%) ST73, and one each (6.7%) of ST10, ST12, ST14, ST1193, and ST1196. From No. 1, two ST131 in the first internal clinic and one ST131 from No. 2 in the aftercare department were highly clonally related, suggesting possible epidemiological association. Antimicrobial resistance was as follows: ciprofloxacin 93.8%, ceftazidime 78.4%, meropenem 0%, fosfomycin 2.9% and nitrofurantoin 1.4%. Prevention of ESBL-producing E. coli dissemination, especially for ST131 clade C2, is inevitably necessary for reducing drug resistance and decreasing healthcare-associated infections.